2018
DOI: 10.1016/j.cub.2018.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Orthonectids Are Highly Degenerate Annelid Worms

Abstract: The animal groups of Orthonectida and Dicyemida are tiny, extremely simple, vermiform endoparasites of various marine animals and have been linked in the Mesozoa (Figure 1). The Orthonectida (Figures 1A and 1B) have a few hundred cells, including a nervous system of just ten cells [2], and the Dicyemida (Figure 1C) are even simpler, with ∼40 cells [3]. They are classic "Problematica" [4]-the name Mesozoa suggests an evolutionary position intermediate between Protozoa and Metazoa (animals) [5] and implies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
5
42
0
Order By: Relevance
“…(Filippova, Purschke, Tzetlin, & Müller, ). Taking together, this may support the annelid affinity of the Orthonectida, also supported by recent molecular phylogenetic analyses (Mikhailov et al, ; Schiffer et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…(Filippova, Purschke, Tzetlin, & Müller, ). Taking together, this may support the annelid affinity of the Orthonectida, also supported by recent molecular phylogenetic analyses (Mikhailov et al, ; Schiffer et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…The Taxonomy browser at the NCBI). As the location of the Mesozoa on the phylogenetic tree is highly debated, we followed the recent analyses placing this (polyphyletic) group within the Lophotrochozoa [32].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Molecular phylogenetic analyses have been in accord with this view (Hanelt et al, 1996;Pawlowski et al, 1996;Petrov et al, 2010), with genomic data of Intoshia linei strongly supporting this affinity (Mikhailov et al, 2016). Studies using transcriptomic data of a dicyemid, Dicyema japonicum, have also suggested that orthonectids are protostomes (Lu et al, 2017); and another analysis on mitochondrial genomes and nuclear genes suggested that orthonectids are members of the phylum Annelida (Schiffer et al, 2018).…”
Section: Introductionmentioning
confidence: 83%